Audit of Enterprises Revenue Cycle - Pečiūra, Vilmantas; Staškevičius, Juozapas Audvydas (Ekonomika, 1998)
One effective way to perform an audit is to classify transactions into “cycles” of related activities. A revenue cycle is common for sales and manufacturing enterprises. Auditors should test financial statements assertions - existence, completeness, rights and obligations, valuation, and presentation and disclosure - embodied in the revenue cycle. Auditors should evaluate the control risk of revenue cycle. If the control risk is low, the number of substantive audit procedures can be reduced. Confirmations is a standard audit procedure for accounts receivable. Positive confirmations provide more reliable evidence. Auditors should evaluate the adequacy of the allowance for doubtful accounts.